Dilema Undang-Undang Informasi dan Transaksi Elektronik dalam Praktik Jurnalisme: Tinjauan dari Teori Panoptikon - Hikami, Indi (Faculty of Da'wa and Communications Sciences, 2022)
Law No. 19 of 2016 electronic information and transactions has caused an overlapping issue in journalism. However, there is Law No. 40 of 1999, which regulates and guarantees press freedom. Unfortunately, many journalists have become a victim of the Law itself. Such a condition will distort Indonesia’s public sphere, where journalism is a supportive instrument. As per Foucault’s panopticon theory, the researcher sees this Law as a supervision instrument to monitor the activity of Indonesia’s press so that they do not produce such a critical news point of view and eventually threaten the authorities. This article uses a narrative approach to break down the relationship between Indonesian Electronic Information and Transactions. The result shows that this Law can either be a supervision instrument. Nevertheless, on the other hand, for journalists, this will potentially limit their freedom since the authorities see their activity as a threat to the government.